The Relationship Between Parental Communication Patterns And Language Delays In Toddlers - Sara Herlina; Meli Saputri; Sellia Juwita (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Speech delay is one of the most common developmental disorders among toddlers and may negatively affect academic performance, social interaction, and future quality of life. One important factor influencing language development is parental communication patterns. According to the Indonesian Pediatric Society (IDAI), approximately 5–8% of toddlers experience speech delay. Data from the Pekanbaru City Health Office in 2024 indicated that the highest number of toddlers was found in the working area of Payung Sekaki Public Health Center, where several cases of speech delay were also reported. This study aimed to analyze the relationship between parental communication patterns and language development delay among toddlers. A quantitative study with a correlational analytic and cross-sectional design was conducted from July to August 2025. The instruments used were a parental communication questionnaire and the Denver II screening tool. The population consisted of 399 toddlers, with 200 respondents selected through purposive sampling. Data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that 124 parents (62%) had good communication patterns. Statistical analysis revealed a significant relationship between parental communication patterns and language development delay (p-value = 0.000; α < 0.05). Most toddlers demonstrated normal language development.